Endogenous mGluR Activity Suppresses GABAergic Transmission in Avian Cochlear Nucleus Magnocellularis Neurons - Lu, Yong (Journal of neurophysiology, 2007)
Department of Neurobiology, Northeastern Ohio Universities College of Medicine, Rootstown, Ohio Submitted 18 August 2006; accepted in final form 27 November 2006 GABAergic transmission in the avian cochlear nucleus magnocellularis (NM) of the chick is subject to modulation by -aminobutyric acid type B (GABA B ) autoreceptors. Here, I investigated modulation of GABAergic transmission in NM by metabotropic glutamate receptors (mGluRs) with whole cell recordings in brain slice preparations. I found that tACPD, a nonspecific mGluR agonist, exerted dose-dependent suppression on evoked inhibitory postsynaptic currents (eIPSCs) in NM neurons. At concentrations of 100 or 200 µM, tACPD increased the failure rate of GABAergic transmission. Agonists for group I (3,5-DHPG, 200 µM), group II (DCG-IV, 2 µM), and group III (L-AP4, 10 µM) mGluRs produced a significant reduction in the amplitude of eIPSCs and a significant increase in failure rate, indicating the involvement of multiple mGluRs in this modulation. The frequency, but not the amplitude, of miniature IPSCs (mIPSCs) was decreased significantly by 3,5-DHPG or DCG-IV. Neither frequency nor amplitude of mIPSCs was affected by L-AP4. mGluR antagonists LY341495 (20 µM) plus CPPG (10 µM) significantly increased the amplitude of eIPSCs, indicating that endogenous mGluR activity suppresses GABA release to NM neurons. Furthermore, blockage of mGluRs increased GABA-evoked discharges recorded under physiological Cl concentrations, whereas tACPD (100 µM) eliminated them. The results indicate that mGluRs play important roles in achieving balanced excitation and inhibition in NM and preserving fidelity of temporal information encoded by NM neurons. Address for reprint requests and other correspondence: Y. Lu, Department of Neurobiology, Northeastern Ohio Universities College of Medicine, 4209 State Route 44, PO Box 95, Rootstown, OH 44272 (E-mail: yluatneoucom.edu )